IDENTIFIKASI CEMARAN MIKROBA PADA DAGING AYAM BROILER : Identification of Microbial Contamination in Broiler Chicken Meat - utami, putri (JURNAL BIOSENSE, 2025)
This study aims to identify microbial contamination in broiler chicken meat. Samples were taken from chicken meat traders in Dadapan Village, and tests were conducted at the Banyuwangi District Health Laboratory. This study used a qualitative descriptive method. The results showed the presence of gram-negative bacteria in the chicken meat samples. On SSA (Salmonella Shigella Agar) media, colonies suspected to be Shigella sp. were found, while on EMB (Eosin Methylene Blue) media, bacterial colonies that were not Escherichia coli were found. Further research is needed for specific identification of bacterial species and education regarding sanitation and proper handling of chicken meat